Bimbingan Kelompok dengan Teknik Homeroom dalam Menanamkan Karakter Peduli Lingkungan - Nurjannah Nurjannah; Kusnadi Kusnadi (Scidacplus, 2025)
Environmental problems are increasingly complex and require the active role of the younger generation, especially students, in fostering an environmentally conscious character. The Nature Lovers Student Association (MAPALA), as an environmentally based organization, plays a strategic role in shaping environmentally friendly attitudes and behaviors. However, members are still found to be inconsistent in applying environmental values in their daily lives. This study aims to describe the implementation of group guidance using the homeroom technique in instilling an environmentally conscious character in MAPALA members of UIN Raden Fatah Palembang and analyze its impact on changes in members' attitudes and behaviors. This study uses a qualitative approach with a case study method. Data collection techniques include observation, in-depth interviews, and documentation. The results show that group guidance using the homeroom technique, implemented through the stages of opening, transition, core activities, and closing, is able to create a friendly, open, and participatory atmosphere. The homeroom technique provides an effective space for reflection and discussion so that MAPALA members are able to understand, internalize, and apply environmental values. Thus, group guidance using the homeroom technique has proven effective as an effort to instill an environmentally conscious character in students.